2010
DOI: 10.1103/physrevb.81.153302
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed spin dephasing for two-dimensional and bulk electrons in GaAs wires due to engineered cancellation of spin-orbit interaction terms

Abstract: We report a study of suppressed spin dephasing for quasi-one-dimensional electron ensembles in wires etched into a GaAs/AlGaAs heterojunction system. Time-resolved Kerr-rotation measurements show a suppression that is most pronounced for wires along the [110] crystal direction. This is the fingerprint of a suppression that is enhanced due to a strong anisotropy in spin-orbit fields that can occur when the Rashba and Dresselhaus contributions are engineered to cancel each other. A surprising observation is tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…In the classic proposal of a spin field-effect transistor due to Datta and Das (1990) already sketched in Fig. 2, an electron is emitted from a spin-polarized electrode into a semiconductor region where its spin is rotated via electrically tunable Rashba coupling.…”
Section: G Spin Field-effect Transistors and Related Conceptsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the classic proposal of a spin field-effect transistor due to Datta and Das (1990) already sketched in Fig. 2, an electron is emitted from a spin-polarized electrode into a semiconductor region where its spin is rotated via electrically tunable Rashba coupling.…”
Section: G Spin Field-effect Transistors and Related Conceptsmentioning
confidence: 99%
“…A paradigmatic example of a semiconductor spintronics device is the spin field-effect transistor (Datta and Das, 1990) schematically depicted in Fig. 2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Measurements of the spin-relaxation times in these systems have indicated that the strong spatial anisotropy is determining specific behavior, leading to the possibility of controlling such system parameters through the growth process of the LSL. 10 In this work we are inspired by the latter results to investigate the modulation effect induced by the Rashba (R) and Dresselhaus (D) SOI on the electric conductivity, as well as the anisotropy of the spin-relaxation rates within a unitary formalism derived in the weak localization approximation. Considering that the physical properties of the LSL are tuned in the growth process, our analysis bridges the theoretical discussion of isolated quantum wires 11,12 with that of the isotropic 2D systems.…”
Section: Introductionmentioning
confidence: 99%
“…The coexistence of the Dresselhaus and Rashba SOIs leads to an anisotropic spin dynamics in 2DEG as a result of the orientation-dependent effective magnetic fields generated by the SOIs. [8][9][10] In particular, when the two types of SOI are nearly equal in magnitude, the resultant effective magnetic fields are aligned along the same direction, leading to a persistent spin helix (PSH) state. [11][12][13][14] In this state, the spin rotation depends only on the displacement, which is independent of the electron path.…”
mentioning
confidence: 99%